Nanoindentation of nickel film by magnetron sputtering ion plating on sapphire: Molecular dynamics simulations and experiments - Shilong Sun; Bin You; Tianlei Dong; Yusheng Sui; Rongchuan Lin; Shasha Wei (Results in Physics)
Magnetron sputtering deposition of metals on sapphire (α-Al2O3) has emerged as significant research focus in advanced manufacturing due to its critical role in enhancing sapphire’s performance. This study examines the effects of varying negative biases (60 V, 80 V, 100 V) and annealing treatments on the mechanical properties of Ni films deposited on sapphire. Molecular dynamics (MD) simulations and experimental validation based on results of deposition experiments. With increasing negative bias reduces the grain size of the Ni film and decreases the (111)/(100) phase ratio. After annealing, residual stress within film is released, resulting in increased grain size and a higher content of (100) phase. MD simulations reveal that higher negative biases lead to increased dislocation density in Ni film, with plastic deformation predominantly governed by Shockley and Stair-rod dislocations. After annealing, dislocation density decreases, and under 80 V and 100 V conditions, the emergence of Hirth dislocations facilitates earlier onset of plastic deformation. Differences in phase composition within Ni film cause atomic displacements during indentation to exhibit directionality, which diminishes after annealing. Furthermore, the von Mises strain initially decreases and then increases with rising negative bias. Notably, at 80 V, the film achieves an optimal balance of moderate grain size, low dislocation density, and controlled phase composition, minimizing von Mises strain and exhibiting the highest elastic modulus and hardness. The experimental findings align with MD simulation results based on the COMB3 potential, confirming the reliability of the simulations. This study provides theoretical insights into the mechanical behavior of nanocrystalline Ni films under mechanical loading.